Locoregional and Distant Recurrence Patterns in Young versus Elderly Women Treated for Breast Cancer. (9th April 2015) - Rudra, Soumon; Yu, David S.; Yu, Esther S.; Switchenko, Jeffrey M.; Mister, Donna; Torres, Mylin A.
Abstract : Objective . This study examined recurrence patterns in breast cancer patients younger than age of 40 and older than age of 75, two groups that are underrepresented in clinical trials and not routinely screened by mammography. Methods . The records of 230 breast cancer patients (n = 125 less than 40 andn = 105 greater than 75) who presented to the Emory University Department of Radiation Oncology for curative treatment between 1997 and 2010 were reviewed. Data recorded included disease presentation, treatment, and areas of locoregional recurrence. Results . Women less than 40 years of age had higher rates of locoregional recurrence (20% versus 7%, P = 0.004 ) and distant recurrence (18% versus 5%, P = 0.003 ) than patients above 75 years of age. On multivariate analysis, patient age less than 40 was the only significant predictor of locoregional recurrence (P = 0.018 ). In a univariate analysis of each age group, receptor status and postlumpectomy radiation were significant predictors of locoregional recurrence-free survival in younger women while mammography screening predicted for distant recurrence-free survival in older patients. Conclusion . The factors identified in our age-stratified analysis highlight patients who are at high risk of locoregional and distant recurrence. Future studies aimed at enhancing therapies in young patients are warranted.